Diode-pumped multi-frequency Q-switched laser with intracavity cascade Raman emission - Chang, Y. T.; Huang, Y. P.; Su, K. W.; Chen, Y. F. (My University, 2008)
A diode-pumped actively Q-switched mixed Nd:Y0.3Gd0.7VO4 laser with an intracavity KTP crystal is developed to produce cascade SRS emission up to the fourth order. With an incident pump power of 14 W and a repetition rate of 50 kHz, the average output powers at the first, second, third and fourth Stokes modes are approximately 0.05 W, 0.61 W, 0.25 W, and 0.11 W, respectively. The maximum peak power is greater than 2 kW. (C) 2008 Optical Society of America.